2012
DOI: 10.1136/jnnp-2011-302085
|View full text |Cite
|
Sign up to set email alerts
|

Treatment changes in a cohort of people with apparently drug-resistant epilepsy: an extended follow-up

Abstract: This suggests that about half of people with apparent drug-resistant epilepsy can have significant improvements in seizure control with further drug changes. Some will subsequently relapse, but long periods of seizure freedom or significantly improved seizure control in the absence of complete seizure control can occur. Such valuable improvements suggest that the recently proposed International League against Epilepsy definition of refractory epilepsy may be too restrictive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 18 publications
(20 reference statements)
4
31
0
1
Order By: Relevance
“…The authors of the study also noted that the remission was negatively correlated with the number of ASDs that failed in a particular patient, while relapse could not be explained by dose reductions or medication discontinuation alone. Similarly, Neligan et al (27) conducted a prospective cohort study in 139 patients with uncontrolled chronic epilepsy with a median follow-up of 6.9 years and showed that 19% of patients became seizure free and 29% of patients experienced 50–99% improvement in seizure frequency at the last follow-up. However, a substantial proportion of the patients who experienced remission subsequently relapsed (27).…”
Section: Background: Refractory Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the study also noted that the remission was negatively correlated with the number of ASDs that failed in a particular patient, while relapse could not be explained by dose reductions or medication discontinuation alone. Similarly, Neligan et al (27) conducted a prospective cohort study in 139 patients with uncontrolled chronic epilepsy with a median follow-up of 6.9 years and showed that 19% of patients became seizure free and 29% of patients experienced 50–99% improvement in seizure frequency at the last follow-up. However, a substantial proportion of the patients who experienced remission subsequently relapsed (27).…”
Section: Background: Refractory Epilepsymentioning
confidence: 99%
“…Similarly, Neligan et al (27) conducted a prospective cohort study in 139 patients with uncontrolled chronic epilepsy with a median follow-up of 6.9 years and showed that 19% of patients became seizure free and 29% of patients experienced 50–99% improvement in seizure frequency at the last follow-up. However, a substantial proportion of the patients who experienced remission subsequently relapsed (27). In another study, Neligan et al (28) found that the intermittent pattern of seizures (i.e., having one or more seizure-free periods which lasted for at least 2 years) occurred in about 30% of patients with refractory epilepsy, which was found to be associated with fewer total ASDs taken and lower seizure frequency in the previous year when compared to the continuous pattern of pharmacoresistance.…”
Section: Background: Refractory Epilepsymentioning
confidence: 99%
“…Risk factors for subsequent poor treatment outcome are symptomatic focal epilepsy and cognitive deficits (Chadwick et al 1996;Schmidt and Löscher 2005). Finally, 5% of those with refractory epilepsy will achieve a remission of 12 mo when medication is adjusted, although about onehalf will subsequently relapse (Neligan et al 2012).…”
Section: Prognosismentioning
confidence: 99%
“…16 A systematic review and meta-analysis of the efficacy of all novel AEDs as adjunctive treatment for drug-resistant epilepsy found total control over ES in about 6% of all patients and a reduction in critical frequency in 21% 17 (LE I). Population studies in patients with drug-resistant epilepsy describe long remission periods thanks to successive changes in medication (8%-28%) 18,19 (LE III). Fig.…”
Section: Number Of Antiepileptic Drugs To Try In Cases Of Drug-resistmentioning
confidence: 99%